2009
DOI: 10.1016/j.cellimm.2009.03.008
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 and its co-receptors determine responses of macrophages and dendritic cells to lipoproteins of Mycobacterium tuberculosis

Abstract: Mycobacterium tuberculosis (Mtb) signals through Toll-like receptor 2 (TLR2) to regulate antigen presenting cells (APCs). Mtb lipoproteins, including LpqH, LprA, LprG and PhoS1, are TLR2 agonists, but their co-receptor requirements are unknown. We studied Mtb lipoprotein-induced responses in TLR2−/−, TLR1−/−, TLR6−/−, CD14−/− and CD36−/− macrophages. Responses to LprA, LprG, LpqH and PhoS1 were completely dependent on TLR2. LprG, LpqH, and PhoS1 were dependent on TLR1, but LprA did not require TLR1. None of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
120
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(124 citation statements)
references
References 46 publications
2
120
0
2
Order By: Relevance
“…38 We have previously shown that under hyperglycemia, TLR2/ TLR6 association results in cytokine secretion in human monocytes 26 consistent with the present data. Also, we did not observe changes in TLR1 mRNA expression and it is not known if TLR6 by itself is inflammatory.…”
Section: Discussionsupporting
confidence: 82%
“…38 We have previously shown that under hyperglycemia, TLR2/ TLR6 association results in cytokine secretion in human monocytes 26 consistent with the present data. Also, we did not observe changes in TLR1 mRNA expression and it is not known if TLR6 by itself is inflammatory.…”
Section: Discussionsupporting
confidence: 82%
“…These effects were abrogated in the presence of PAFR antagonists or anti-CD36 blocking antibody [17]. Comparing to macrophages, DCs express less CD36 [32,33] and TLR4 in the membrane [34], thus these mechanisms above mentioned for macrophages are less significant in DCs. Additionally, it was demonstrated that PAFR activation induced CD36 expression in macrophages by mechanisms dependent on PPARγ [17].…”
Section: Discussionmentioning
confidence: 80%
“…However, Mtbinduced macrophage activation was not augmented by overexpression of ectopic MD-2, and cells expressing a lipopolysaccharide-unresponsive MD-2 mutant responded normally to Mtb (Means et al, 2001). Therefore, TLR4 signaling, and the accessory protein MD-2, may not play a significant role in immunity to Mtb compared with other TLR signaling pathways, such as TLR2 signaling (Jo et al, 2007;Drage et al, 2009;Velez et al, 2010). This is supported by the findings of our study, in which genetic variation in the MD-2 gene promoter region was found to be unrelated to susceptibility to TB.…”
Section: Discussionmentioning
confidence: 91%